Molecular and Physiological Responses of Litopenaeus vannamei to Nitrogen and Phosphorus Stress - Qianqian Zhao; Cun Wei; Jiangling Dou; Yue Sun; Qifan Zeng; Zhenmin Bao (Antioxidants)
Environmental stressors such as nitrogen and phosphorus play a critical role in regulating the growth and physiological functions of Litopenaeus vannamei, a key species in aquaculture. This study investigates the effects of nitrogen and phosphorus stress on shrimp growth, oxidative stress, tissue damage, and molecular mechanisms. Exposure to increasing concentrations of nitrogen and phosphorus significantly reduced growth rates. Oxidative stress markers, including superoxide dismutase (SOD), catalase (CAT), total antioxidant capacity (T-AOC), and malondialdehyde (MDA), indicated heightened oxidative damage under both stress conditions, with nitrogen stress causing more severe responses than phosphorus stress. Histopathological analysis revealed substantial damage to the gills and hepatopancreas, organs essential for respiration and metabolism. Transcriptomic analysis identified differentially expressed genes (DEGs) enriched in apoptosis, lysosome, sphingolipid metabolism, and phagosome pathways, suggesting shared molecular responses to nitrogen and phosphorus stress. The results demonstrate that L. vannamei initiates oxidative and immune responses to cope with environmental stressors, but the adaptive capacity remains limited. These findings provide a foundation for understanding the stress tolerance mechanisms in shrimp and inform future strategies for breeding high-resistance strains in aquaculture.